The framing and evaluation of multiple hypotheses - MOCK, Theodore J. (Institutional Knowledge at Singapore Management University, 2008)
This study provides exploratory evidence on auditors’ framing and evaluation of hypotheses, identifies implications for improving audit decision-making and facilitates the interpretation of prior research. Prior studies usually assume hypotheses to be framed as mutually exclusive and exhaustive. However, both verbal protocol evidence and probability assessments reveal that in a realistic case most auditors frame the hypotheses as a non-mutually exclusive and exhaustive set of causes. Further, auditor probability assessments tend to reflect multiple causes. Finally, exploratory analyses indicate auditors have difficulty in updating assessments consistent with the perceived interrelationships between hypotheses.